Upaya Peningkatan Kesehatan Masyarakat dengan Pembentukan Kader Pendamping Keluarga dalam Rangka Pencegahan Anemia pada Remaja di Kelurahan Banjarsari, Kalibawang, Kulon Progo - Munica Rita Hernayanti; Dwiana Estiwidani; Maranata Maranata (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2023)
Cadres play an important role in assisting families to prevent adolescent anemia. Cadres can be empowered to assist adolescents in efforts to prevent anemia in adolescents. The purpose of this service is to form adolescent companion cadres, increase cadre knowledge related to adolescent anemia. The targets in this service are 32 cadres in Banjarsari Village, Kalibawang, Kulon Progo. The implementation time is May to October 2021. The approach used in this service is training and mentoring to cadres. The results of this service program are the formation of adolescent companion cadres and increasing cadre knowledge in terms of adolescent anemia prevention behavior and family assistance. Keyword : community empowerment; cedres; adolescent anemia